Formas de perdón, arrepentimiento y disculpas en la historia del español. Una aproximación desde el análisis textual - Medina López, Javier (El Colegio de México, 2023)
This article studies apology speech-acts in the Spanish language from the 12th to the 19th century. Using data provided by the Corpus diacrónico del español (CORDE), it analyses the lexical fields to forgive, to blame, to apologise, to excuse, to regret and to be sorry and attempts to classify several thematic areas within the general concept of apologies.  It concludes that apologies are linked from the very beginning to Catholicism and from there spread to civil society in a slow and complex process of secularization.